Analysis of Conceptual Errors In Mathematical Solving Through Problem-Based Learning Model In Students - Muhammad Affan Surbakti; Zul Amry; Mulyono (UIN Sunan Gunung Djati Bandung, 2026)
This study seeks; To identify errors, alternate answer processes, and student problem-based learning activities. This qualitative descriptive miles huberman research was conducted at SMP Negeri 27 Medan, class VIII, in 2025/2026. This study included 29 students. The most common errors in this study are calculation errors and not writing the final conclusion, so problem-based learning models can improve students' conceptual understanding but have not completely minimized errors in the process and coding skills stage. Therefore, procedural accuracy and mathematical communication skills must be emphasized to minimize student errors. Overall, the study shows that the Newman approach can reveal student errors in handling SPLDV problems. Problem-based learning models can also improve conceptual understanding and student learning, reducing mathematical errors.